Book Review: A Long Time Coming: The story of Ngāi Tahu's Treaty Settlement Negotiations with the Crown - Jones, Carwyn (Victoria University of Wellington Law Review, 2021)
Martin Fisher A Long Time Coming: The story of Ngāi Tahu's Treaty Settlement Negotiations with the Crown (Canterbury University Press, 2020).